2007
DOI: 10.1080/09553000701570238
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the radioprotective effect of histamine on small intestine

Abstract: Histamine prevents radiation-induced toxicity by increasing proliferation of damaged intestinal mucosa and suppressing apoptosis that was associated with an increase in SOD and Catalase levels. This effect might be of clinical value in patients undergoing radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 40 publications
8
40
0
Order By: Relevance
“…3,4 In this regard, it was reported that histamine significantly protects small intestine and bone marrow, from high doses of ionizing radiation, in 2 models of rodents. [5][6][7] In addition, histamine has the ability to prevent ionizing radiation-induced functional and histological alterations of salivary glands. 8 These features make histamine a suitable candidate as a radioprotector for patients undergoing radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In this regard, it was reported that histamine significantly protects small intestine and bone marrow, from high doses of ionizing radiation, in 2 models of rodents. [5][6][7] In addition, histamine has the ability to prevent ionizing radiation-induced functional and histological alterations of salivary glands. 8 These features make histamine a suitable candidate as a radioprotector for patients undergoing radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Histamine radioprotective effect on small intestine was related to an increased rate of proliferation as evidenced by the enhanced proliferation markers immunoreactivity [5-bromo-2'-deoxyuridine (BrdU), and proliferating cell nuclear antigen (PCNA)]. Additionally, this outcome was accompanied by a reduction in the number of apoptotic cells per crypt and a modification of antioxidant enzyme levels that could lead to enhance the antioxidant capacity of intestinal cells (Medina et al, 2007). Histamine also protects rat small intestine against ionising radiation damage and this effect was principally associated to a decrease in intestinal cell crypt apoptosis (Medina & Rivera, 2010a).…”
Section: Histamine As a Radioprotectormentioning
confidence: 96%
“…To summarize, histamine treatment can selectively modulate cellular damage produced by ionising radiation, thus preventing radiation induced damage on small intestine, bone marrow and salivary glands. Furthermore, histamine in vitro enhances the radiosensitivity of breast cancer cells (Medina et al, 2006) while does not modify that of melanoma (Medina et al, 2007). Despite histamine may be proliferative in some cancer cell types, it may still be beneficial as radioprotector in view of the fact that it is only administered for a short period of time to reduce the radiation induced damage.…”
Section: Histamine As a Radioprotectormentioning
confidence: 99%
See 1 more Smart Citation
“…We have also proved that histamine prevents radiation-induced toxicity on small intestine by modulating the antioxidant enzymes expression and by suppressing apoptosis and increasing proliferation of damaged intestinal mucosa (Medina et al, 2007). Intracellular ROS concentration is critical for cell growth and survival; in normal cells ROS levels are kept low, but quite the opposite in tumor cells high levels of ROS close to the threshold of cytotoxicity are related to cell proliferation.…”
Section: Ionizing Radiation Enhances the Activity Of Mmps And Cell MImentioning
confidence: 96%